Do minimum wage increases influence worker health? - Michael R. Strain; Brady P. Horn; Johanna Catherine Maclean (American Enterprise Institute (AEI), 2016)
While the employment effects of minimum wage increases have been heavily studied, the impact of minimum wage increases on non-labor market outcomes has received less attention. This study is the first to investigate whether minimum wage increases in the U.S. affect an important non-market outcome: worker health. Economic models of the demand for health suggest a link between minimum wage increases and worker health, but the direction and magnitude of the impact is ultimately an empirical question. To study this question, we use data on lesser-skilled workers from the 1993-2014 Behavioral Risk Factor Surveillance Surveys coupled with differences-in-differences and triple-difference models. We find little evidence that minimum wage increases lead to improvements in overall worker health. In fact, we find some evidence that minimum wage increases may decrease some aspects of health, especially among unemployed male workers. We also find some evidence that increases reduce mental strain among employed workers.
Keywords: A; 330; Minimum Wage